Heritability and Interrelationships for Agronomic, Physiological and Yield Traits of Quinoa (Chinopodium quinoa Willd.) under Elevated Water Stress - , A. M. M. Al-Naggar; , R. M. Abd El-Salam; , A. E. E. Badran; , Mai M. A. El-Moghazi (Archives of Current Research International, 2017)
Strong associations between yield and given traits along with high heritability for such traits would allow plant breeder to use these traits as selection criteria for selecting high yielding genotype. The present investigation aimed at elucidating the relationships among agronomic, physiological and yield traits of five quinoa genotypes and estimating heritability in broad sense (h2b) and genetic advance (GA) from selection for these traits. A two-year experiment was carried out in a split plot experiment with five replications. The main plots were devoted to three irrigation regimes, i.e. well watering (WW), water stress (WS) and severe water stress (SWS), achieving a field capacity of 95, 65 and 35%, respectively, and sub plots to five quinoa genotypes. The results indicated that correlations (r) between each of seed yield/plant (SYPP), water use efficiency (WUE), drought tolerance index (DTI) and other studied traits became stronger as water stress became severer; the strongest correlations were with thousand seed weight (TSW), inflorescence weight (IW), inflorescence diameter (ID), branches/plant (BPP), root length (RL), inflorescence length (IL) and inflorescences/plant (IPP). The highest h2b (>0.99%) under all irrigation treatments was shown by RL, WUE and seed yield/ha (SYPH), while the lowest estimate (0.0%) was shown by IPP under WW and WS and SPP under WW and SWS. Estimates of GA increased as water stress increased; the highest GA was shown by IPP (101.87%) followed by BPP (68.04%) under SWS, while the lowest one (1.32%) was shown by days to maturity under WS. Results indicated that the best secondary traits for high drought tolerance and high WUE of quinoa were TSW, IW, ID, IL, IPP, BPP, RL, SYPP and SYPH traits, since they showed high (r), high (h2b) and high (GA) estimates. Further studies should be carried out on other quinoa germplasm to ascertain this conclusion.